Longitudinal relationships between self-concept for physical activity and neighborhood social life as predictors of physical activity among older African American adults - Allison M. Sweeney; Dawn K. Wilson; M. Lee Van Horn (BMC, 2017)
Abstract Background Engaging in regular physical activity (PA) as an older adult has been associated with numerous physical and mental health benefits. The aim of this study is to directly compare how individual-level cognitive factors (self-efficacy for PA, self-determined motivation for PA, self-concept for PA) and neighborhood perceptions of the social factors (neighborhood satisfaction, neighborhood social life) impact moderate-to-vigorous physical activity (MVPA) longitudinally among older African American adults. Methods Data were analyzed from a sub-set of older African American adults (N = 224, M age = 63.23 years, SD = 8.74, 63.23% female, M Body Mass Index = 32.01, SD = 7.52) enrolled in the Positive Action for Today's Health trial. MVPA was assessed using 7-day accelerometry-estimates and psychosocial data (self-efficacy for PA, self-determined motivation for PA, self-concept for PA, neighborhood satisfaction, neighborhood social life) were collected at baseline, 12-, 18-, and 24-months. Results Multilevel growth modeling was used to examine within- and between-person effects of individual-level cognitive and social environmental factors on MVPA. At the between-person level, self-concept (b = 0.872, SE = 0.239, p < 0.001), and neighborhood social life (b = 0.826, SE = 0.176, p < 0.001) predicted greater MVPA, whereas neighborhood satisfaction predicted lower MVPA (b = −0.422, SE = 0.172, p = 0.015). Among the between-person effects, only average social life was moderated by time (b = 0.361, SE = 0.147, p = 0.014), indicating that the impact of a relatively positive social life on MVPA increased across time. At the within-person level, positive increases in self-concept (b = 0.294, SE = 0.145, p = 0.043) and neighborhood social life (b = 0.270, SE = 0.113, p = 0.017) were associated with increased MVPA. Conclusions These results suggest that people with a higher average self-concept for PA and a more positive social life engaged in greater average MVPA. Additionally, changes in perceptions of one's neighborhood social life and one's self-concept for PA were associated with greater MVPA over 2 years. These factors may be particularly relevant for future interventions targeting long-term change and maintenance of MVPA in older African Americans. Trial registration ClinicalTrials.Gov # NCT01025726 registered 1 December 2009.